INTERDEPENDENCE BETWEEN POLITICAL ENVIRONMENT AND COMPETITIVENESS OF COMPANIES IN A COMPLEX BUSINESS SYSTEM - MARINA POPA (Global Economic Observer)
Amidst a landscape of constant change—marked by the incredible speed of pandemics and military conflicts on one hand and the advancements of the metaverse with its artificial intelligence elements on the other—the global business environment must redefine itself at an even faster pace. Against this background, companies are continuously pressured to maintain their level of competitiveness in foreign or local markets and are directly influenced by the business environment. The interdependence between company competitiveness and the political environment is becoming increasingly powerful because a country's level of prosperity depends on its political system. In this article, the author aims to analyse how the elements of the political environment directly affect the business environment and companies' competitiveness, ultimately determining a country's level of development. The author attempts to analyse a company's level of competitiveness through the prism of the type of political system used in certain countries, such as the USA, Germany, and Venezuela.